Heart rate recovery as a guide to predict fatigue and changes in performance parameters - Lamberts, R.; Swart, J.; Capostagno, B.; Noakes, T. D.; Lambert, M. I. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Determining the optimal balance between training load and recovery is part of achieving peak performances in well-trained and elite athletes. In the process of monitoring this balance, the measurement of heart rate recovery (HRR) after exercise has shown to be responsive to recently applied training loads (1,2). However, the link between a decrease in HRR, fatigue and an impairment in performance, has not been confirmed. Therefore, the aim of this study was to monitor HRR and cycling performance in a group of well-trained cyclists who participated in a 4 week high intensity training (HIT) program. Methods: Fourteen well-trained cyclists participated in a 4 week program consisting of 8 HIT sessions. Before and after the training period peak and endurance parameters were measured. HRR was measured after each HIT session (HRRHIT) and expressed a relative change compared to after the first HRRHIT. Retrospectively cyclists were assigned to a group that continuously increase their HRRHIT (GIncr) or a group that showed a decrease in HRRHIT (GDecr). Results: The relative peak power output improved in both groups had (GIncr; P = 0.001 and GDecr; P = 0.016, respectively), as did parameters of endurance performance (P = 0.001 and P < 0.048, respectively). A significant interaction effect of Group X Time was found for 40-km TT power (P = 0.010), indicating that GIncr improved significantly more than GDecr after the HIT period. Improvement in 40-km TT time showed a similar tendency and although effect size statistics showed a "moderate" to almost"large" chance that this difference is clinically meaningful, this effect was not statistically significant (P = 0.059). Conclusions: This is the first study show that a decrease in HRR after exercise, during a HIT training period, is associated with a blunted improvement in endurance performance. However, changes peak performance seem initially to be unaffected. This suggests that a decrease in HRR, which possibly reflects accumulative fatigue (3,4), initially compromises endurance performance rather than peak performance. Therefore, HRR has the potential to monitor changes in endurance cycling performance and contribute to a more accurate prescription of training load in well-trained and elite cyclists.